2021
DOI: 10.1101/2021.05.09.443303
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human iPSC-derived mesodermal progenitor cells preserve their vasculogenesis potential after extrusion and form hierarchically organized blood vessels

Abstract: Post-fabrication formation of a proper vasculature remains an unresolved challenge in bioprinting. Established strategies focus on the supply of the fabricated structure with nutrients and oxygen and either rely on the mere formation of a channel system using fugitive inks, or additionally use mature endothelial cells and/or peri-endothelial cells such as smooth muscle cells for the formation of blood vessels in vitro. Functional vessels, however, exhibit a hierarchical organization and multilayered wall struc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 52 publications
(63 reference statements)
1
5
0
Order By: Relevance
“…The optical microscopy images show the morphologies in terms of width, length, and spread area of the Y1 and HT-22 cells on the surfaces of pure CA and hybrid A 1 :G 0.5 hydrogel particles (Figure b). We observed that the cells clustered and formed 3D cell spheres on the CA hydrogel particle surfaces (Cultures 1 and 2) due to insufficient cell–matrix interactions, similar to previously reported works. ,, The size of the cell spheres increased with increasing culture days. As a biomaterial, alginate hydrogel is mechanically tough but not adhesive enough to provide cell attachment. ,, Cells cultured on the surfaces of hybrid A 1 :G 0.5 hydrogel particles exhibited spreading (Culture 3) because of the cell-adhesive property of Gel (Gel possesses the RGD sequence of collagen). , Immediately after the culture, both the cells on the hybrid A 1 :G 0.5 hydrogel particle surfaces showed spherical morphology (as also observed on CA hydrogel particle surfaces).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The optical microscopy images show the morphologies in terms of width, length, and spread area of the Y1 and HT-22 cells on the surfaces of pure CA and hybrid A 1 :G 0.5 hydrogel particles (Figure b). We observed that the cells clustered and formed 3D cell spheres on the CA hydrogel particle surfaces (Cultures 1 and 2) due to insufficient cell–matrix interactions, similar to previously reported works. ,, The size of the cell spheres increased with increasing culture days. As a biomaterial, alginate hydrogel is mechanically tough but not adhesive enough to provide cell attachment. ,, Cells cultured on the surfaces of hybrid A 1 :G 0.5 hydrogel particles exhibited spreading (Culture 3) because of the cell-adhesive property of Gel (Gel possesses the RGD sequence of collagen). , Immediately after the culture, both the cells on the hybrid A 1 :G 0.5 hydrogel particle surfaces showed spherical morphology (as also observed on CA hydrogel particle surfaces).…”
Section: Resultssupporting
confidence: 89%
“…We observed that the cells clustered and formed 3D cell spheres on the CA hydrogel particle surfaces (Cultures 1 and 2) due to insufficient cell−matrix interactions, similar to previously reported works. 20,67,68 The size of the cell spheres increased with increasing culture days. As a biomaterial, alginate hydrogel is mechanically tough but not adhesive enough to provide cell attachment.…”
Section: Influence Of Concentrations Of Sa and Crosslinking Agent Cac...mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that the presence of mesodermal progenitor [ 66 68 ] or pericytes [ 54 , 55 ] is critical for vasculature formation in various organoids. In agreement with these findings, we found that hPSC-derived HscLCs were crucial to the development of functional microvasculature in mLOs.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to a combination of low viscosity and extended thermal gelation time 13,16 , ultimately requiring a high level of self-support and temperature control when transitioning from a liquid to a gel 56,57 a challenge prevalent throughout biofabrication, with technologies often requiring specific bioink hydrogel formulations. Collagen itself is often combined with other hydrogels such as alginate 58 to enable bioprinting. The RIFLE system circumvents this problem for stratified tissue with the stable suspension of the liquid phase hydrogel in the desired microscale spatial constraint prior to application of the gelation reagent or process.…”
Section: Vascular Tunica Media Tissue Engineering With Riflementioning
confidence: 99%